Formation and interpretation of Sufi discourse in the poetry of Adonis - Kdhim Hadi, Salah (Al-Adab Journal, 2021)
The study of discourse calls for the researcher to study the components of the poetic text, and its cultural and linguistic cognitive contexts, to reach the final stop of the meaning, meaning that the significance of the text alone does not work. The research is limited to identifying the type of Sufi discourse with Adonis, this poet known for his abundant culture, as he is considered one of the critical poets who were able to master the language, knowledge and heritage news, and at the same time he led the Arab poetic renewal movement.Attention should be paid to the mechanisms or tools of modernity that Adonis used in his poetry, such as: the titles of the poems, or the thresholds of the texts, as it is the chandelier that illuminates the general theme of the poem, and sometimes it is a key to the obsolete meanings that he spreads in his poetry, and other times it makes it a mystery that pushes the recipient to think and open horizons of interpretation Or, it makes it an answer to a question, and may be the last word in the poem.Adonis uses a variety of methods in the compositions of his poetic sentences that adopt different references, such as historical, religious and heritage references, and he employs them in his mystical topic. He often uses a specific dictionary of Sufi terms, in addition to using forms in the structure and type of the poem, such as (The Mirror), (The Mask), and (Al-Buh) poems, and he uses dialogues and interactions to give his poem a purely Indonesian mystical identity.